A comparative study on the mineralogy, chemical speciation, and combustion behavior of toxic elements of coal beneficiation products. (15th September 2018) - Fu, Biao; Liu, Guijian; Sun, Mei; Hower, James C.; Hu, Guangqing; Wu, Dun
Abstract: The huge demand for high-quality coal in China has resulted in increased generation of preparation plant wastes of various properties. A series of beneficiation products collected from a preparation plant were characterized to understand their petrographic and mineralogical characteristics, as well as thermochemical and trace element behavior during combustion. The minerals in the Luling preparation plant wastes from Huaibei coalfield mainly included kaolinite and quartz, with minor calcite, ankerite, pyrite, illite, chalcopyrite, albite, K-feldspar, anatase/rutile, and iron-oxide minerals. Massive clay lumps of terrigenous origin, cleat-infilling carbonate, and pyrite of epigenetic origin were prone to be enriched in the middlings and coal gangue. Minor or trace heavy minerals also reported to the preparation plant wastes. The contents of low-density density vitrinite and liptinite were enhanced in the clean coal, while inertinite-maceral group were enriched in the middlings. The modes of occurrences of toxic elements differed between raw coal and the waste products; and their transformation behavior during heavy medium separation is largely controlled by clay minerals (V, Cr, Co, Sb, and Pb), carbonate minerals (Co and Pb), sulfide minerals (As, Cu, Ni, Cd, and Zn) and organic matters (V, Cr, Se, and Cu). Three groups were classified based on the volatile ratio (Vr) of toxic elements. Group 1 includes the highly volatile element Se with Vr > 85%; Group 2 contained elements As, Pb, Zn, Cd and Sb, with the Vr in the range of 20–85% and V, Cr, Co, Ni and Cu with Vr less than 20% were placed into Group 3. Thermal reactivity of coal inferred from the combustion profiles could be significantly improved after coal beneficiation, whereas the increased inorganic components probably inhibited the thermal chemical reaction of wastes.